2011
DOI: 10.1158/1078-0432.ccr-11-0175
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Evi-1 Is Overexpressed, Promotes Proliferation, and Is Prognostically Unfavorable in Infratentorial Ependymomas

Abstract: Purpose: Ependymomas are glial tumors of presumably radial glial origin that share morphologic similarities with ependymal cells. The molecular genetics of ependymomas of supratentorial, infratentorial, and spinal location is heterogeneous. We aimed at identifying pathways operative in the development of infratentorial ependymomas.Experimental Design: To do so, gene expression profiles of tumor cells laser microdissected from infratentorial ependymomas (n ¼ 15) were compared with that of nonneoplastic ependyma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Prdm14 is overexpressed in breast cancer (Nishikawa et al, 2007) and causes lymphoid leukaemia (Dettman et al, 2011). Prdm3 is a susceptibility locus in nasopharyngeal carcinoma (Bei et al, 2010) and a variety of other solid tumours (Koos et al, 2011;Sugita et al, 2000). In addition, Prdm13 is a tumour antigen associated with medulloblastoma (Behrends et al, 2003).…”
Section: Box 2 Prdms In Cancer and Other Diseasesmentioning
confidence: 99%
“…Prdm14 is overexpressed in breast cancer (Nishikawa et al, 2007) and causes lymphoid leukaemia (Dettman et al, 2011). Prdm3 is a susceptibility locus in nasopharyngeal carcinoma (Bei et al, 2010) and a variety of other solid tumours (Koos et al, 2011;Sugita et al, 2000). In addition, Prdm13 is a tumour antigen associated with medulloblastoma (Behrends et al, 2003).…”
Section: Box 2 Prdms In Cancer and Other Diseasesmentioning
confidence: 99%
“…Collectively, our data indicate that EVI1 is a multipurpose transcription factor that synergizes with FOS in invasive tumors. E cotropic viral integration site 1 (EVI1) is a zinc finger (ZNF) transcription factor (TF), and its overexpression in myeloid leukemia (1)(2)(3) and epithelial cancers (1,2,(4)(5)(6)(7)(8)(9) has been extensively studied and correlated with adverse patient outcome (7,10,11). EVI1 also controls several aspects of embryonic development, including hematopoiesis, angiogenesis, and heart and neural development (12).…”
mentioning
confidence: 99%
“…Studying the gene expression profile of ependymoma tumor cells with nonneoplastic ependymal cells, Koos et al [17 ] identified the marked overexpression of the transcription factor Evi-1 (ecotropic viral integration site 1). Moreover, they detected MDS1/EVI1 fusion transcripts in half of the ependymomas and could inhibit the growth of primary ependymoma cells with an EVI1-specific siRNA.…”
Section: Prognostic Markersmentioning
confidence: 99%